Principle of activity as a logical and methodological basis for social processes management - Berkov, Vladimir F. (Journal of the Belarusian State University. Sociology, 2019)
It is shown that the principle of activity can be a logical and methodological basis for social processes management. The content of this principle is determined by the relationship of goal, meansand result. At the social level, they find their continuation and concretization in a variety of concepts, where the main role belongs to the notion of interest.